Malaysia's 14th general election and UMNO's fall intra-elite feuding in the pursuit of power - Gomez, Edmund Terence; Mohamed Nawab; Case, William (Routledge Malaysian studies series, 2019)
"The 2018 Malaysian General Election will stand as a major defining event in Malaysian history, when the ruling Barisan Nasional coalition unexpectedly lost power in the country they had ruled for over half a century. This volume brings together scholars who assess one fundamental factor that brought about this game-changing event in Malaysian politics: intra-elite feuding in the leading Malay-based political parties. This study provides an analysis of individual state politics as well as national trends shaped by the actions of leaders in government and the opposition. An indispensable guide for scholars studying the politics of Malaysia and of Southeast Asia more broadly, it will be of great interest for all readers with an interest in Malaysian politics"